2016
DOI: 10.1186/s12966-016-0364-z
|View full text |Cite
|
Sign up to set email alerts
|

Age, period and cohort effects on adult physical activity levels from 1991 to 2011 in China

Abstract: BackgroundTo date no work has differentiated the effects of age, period, and cohort on physical activity (PA) among Chinese adults, while also considering biological, behavioral, economic, and environmental factors over time.MethodsWe used data from the China Health and Nutrition Survey (CHNS) between 1991 and 2011 (20 years). The outcomes of interest are metabolic equivalent of task (MET) hours per week from work and domestic activities. Age, individual characteristics, household size, asset ownership, urbani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 36 publications
3
28
0
Order By: Relevance
“…27 This could be attributed to the reduced physical activity and muscle mass reported in older women. 28,29 Physical inactivity leads to a decline in glucose tolerance and an increase in fasting blood glucose, 30,31 while skeletal muscle mass was reported to negatively predict 2-hour plasma glucose levels in subjects with normal glucose tolerance. 32 These age-related changes in glucose metabolism would be exacerbated by pregnancy, which may explain the stronger association between the number of pregnancies and GDM among women aged ≥30 years.…”
Section: Discussionmentioning
confidence: 99%
“…27 This could be attributed to the reduced physical activity and muscle mass reported in older women. 28,29 Physical inactivity leads to a decline in glucose tolerance and an increase in fasting blood glucose, 30,31 while skeletal muscle mass was reported to negatively predict 2-hour plasma glucose levels in subjects with normal glucose tolerance. 32 These age-related changes in glucose metabolism would be exacerbated by pregnancy, which may explain the stronger association between the number of pregnancies and GDM among women aged ≥30 years.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that 18% of the population in developing countries are physically inactive (Dumith et al 2011). For instance, the average level of physical activity for adults in China has dropped by nearly 50% from 1991 to 2011 (Zang and Ng 2016), and almost 80% of its adolescents were reported having inadequate exercise (Chen et al 2014). In this context, walking has become a most sustainable form of physical activity in our daily lives, which enables people to interact with the environment in a more direct way due to its slow speed (Kamruzzaman et al 2016;Larrañaga et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Work and domestic physical activity levels of adults fell by nearly half over 20 years (1991-2011) and were negatively associated with living in more urbanised areas. 106 Alarmingly, in urban adults participation in moderate or vigorous physical activity outside of work was as low as 7·9% in the International Collaborative Study of Cardiovascular Disease in Asia 107 done between 2000 and 2001.…”
Section: Low Levels Of Physical Activitymentioning
confidence: 99%